O papel do diretor na educação infantil e sua relação com a família sob a ótica da gestão democrática - Polo, Karla Rosa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In the brazilian legislation is subscribed to the principle of democratic management of public education is in the Federal Constitution, in the Law of Guidelines and Bases or on the new National Plan of Education, however, is still very low participation of parents and community in School Councils. Studies indicate that children's learning is more effective when parents show interest in the routines of school and are seeking information about the pedagogical work developed with the children. The aim of this work is to investigate the experience of nursery schools of the municipal network of a medium-sized city in the interior of São Paulo state about the actions and strategies of the direction to encourage the participation of families with school management; register the work of the pedagogical team and the teachers and their interaction with the parents and analyze each institution targeted by this research according to the quality parameters established by the MEC for education. The research falls within a qualitative approach and non-experimental cross-sectional. The intention was to collect the data of experiences of democratic management in a micro universe and produce an interpretation of the meanings, outcomes, and the expectations that the process generates in the actors. It was undertaken in five early childhood education institutions that are part of the steps of the daycare and pre-school. In addition to the literature search and documentary to the theoretical foundation and discussion of quantitative and qualitative data, the field research included the interview as data collection instrument. Participated in the research 5 school principals, investigated about the construction of the dynamics of interaction between school and community. The results showed that there is a commitment on the part of the directors in the construction of a more participatory and inclusive, but that for... (Complete abstract electronic access below)

Na legislação brasileira está inscrito o princípio da gestão democrática do ensino público seja na Constituição Federal, na Lei de Diretrizes e Bases ou no novo Plano Nacional da Educação, porém ainda é baixa a participação dos pais e comunidade nos Conselhos Escolares. Estudos apontam que a aprendizagem das crianças é mais efetiva quando os pais demonstram interesse nas rotinas escolares e buscam informações sobre o trabalho pedagógico desenvolvido com os filhos. Assim o objetivo do presente trabalho é investigar a experiência das creches da rede municipal de Botucatu, cidade do interior do estado de São Paulo sobre as ações e estratégias da direção para incentivar a participação das famílias junto à gestão escolar; e analisar cada instituição alvo dessa pesquisa de acordo com os parâmetros de qualidade estabelecidos pelo MEC para a educação infantil. A pesquisa se enquadra numa abordagem qualitativa não experimental transversal assim, a intenção foi coletar os dados de experiências de gestão democrática em um universo micro e produzir uma interpretação dos significados, resultados e das expectativas que o processo gera nos atores. Foi realizada em cinco instituições de educação infantil que integram as etapas da creche e pré-escola. Além da pesquisa bibliográfica e documental para fundamentação teórica e discussão dos dados quantitativos e qualitativos, a pesquisa de campo contou com a entrevista como instrumento de coleta de dados. Participaram da pesquisa 5 diretores de escola, investigados sobre a construção de dinâmicas de interação entre escola-comunidade. Os resultados apontaram que existe um empenho por parte das diretoras na construção de uma gestão mais participativa e inclusiva, mas que por diversos fatores uma gestão verdadeiramente democrática não ocorre
Keywords: Gestão democrática; Educação de crianças; Comunidade e escola; Creches; Education